BUBUR MERAH PUTIH SEBAGAI SIMBOL PEMBERIAN NAMA ANAK DALAM PERSPEKTIF SOSIOLOGI BUDAYA - Dhiyaul Auliyah; Arief Sudrajat (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
Culture is a human activity that is carried out repeatedly. The form of culture is in the form of ideas, behaviors, and objects. The purpose of this study is to identify red and white porridge as a symbol of naming children and to analyze the phenomenon from the perspective of cultural sociology through Jurgen Habermas' theory of cultural rationalization. This study uses a qualitative descriptive approach, with interviews and literature studies. The results showed that the red and white porridge symbolized the red porridge symbolized the mother's blood, and the white porridge symbolized the father's semen. Red and white porridge is a symbol of naming children as well as an introduction to prayer for children. According to Habermas, the nature of human relations with other humans is the communication that occurs during the process of transferring knowledge from parents to children about the symbolization of red and white porridge. In addition, during the process of distributing the porridge to the neighbors around the place of residence, after it was made and prayers were said. The recipient will simultaneously receive information about the birth and name of the child, as well as the symbolization of the red and white porridge.